Efficacy and Tolerability of Intravenous Levetiracetam in Children - Aceves, Jose; Khan, Owais; Mungall, Diana; Fonkem, Ekokobe; Wright, Chanin C.; Wenner, Andrea; KIRMANI, BATOOL F. (Frontiers in Neurology, 2013)
Intractable epilepsy in children poses a serious medical challenge. Acute repetitive seizures and status epilepticus leads to frequent emergency room visits and hospital admissions. Permanent neurological damage can occur if there is delay in treatment. It has been shown that these children continue to remain intractable even after acute seizure management with approved FDA agents. Intravenous levetiracetam, a second-generation anticonvulsant was approved by the FDA in 2006 in patients 16 years and older as an alternative when oral treatment is not an option. It has been shown that oral levetiracetam can be used in the treatment of status epilepticus and acute repetitive seizures. Data have been published showing that intravenous levetiracetam is safe and efficacious, and can be used in an acute inpatient setting. This current review will discuss the recent data about the safety and tolerability of intravenous levetiracetam in children and neonates, and emphasize the need for a larger prospective multicenter trial to prove the efficacy of this agent in acute seizure management.